Effect of Exercise and Nutrition on Oxidative Stress in Females with Polycystic Ovary Syndrome, a Current Status and Future Perspective in Narrative Review: Oxidative Stress in Females with Polycystic Ovary Syndrome - Mustafa, Maria; Babur, Naveed; Shah, Saleh; Shafiq, Almina; Aslam, Rabia (Pakistan Journal of Health Sciences, 2025)
Women in their reproductive years are prone to the widespread endocrinological disorder known as Polycystic Ovarian Syndrome (PCOS). To provide in-depth insights into the factors contributing to hormonal imbalances, inflammation, and oxidative stress in women with PCOS. Additionally, it evaluates the impact of exercise and nutritional interventions on oxidative stress and overall metabolic health in PCOS women to improve their quality of life. This review analyzed existing literature and clinical evidence related to endocrine disturbances in PCOS, including hormonal changes such as elevated androgens, insulin resistance, inflammation, and oxidative stress. The effects of lifestyle interventions specifically physical exercise, dietary modifications, and supplementation on these metabolic and hormonal abnormalities were studied. Hormonal Imbalance: Women with PCOS show dysregulated production of Growth Hormone (GH), ghrelin, LEAP-2, Gonadotropin-Releasing Hormone (GnRH), insulin, LH/FSH ratio, androgens, and estrogens. Inflammation and Oxidative Stress: Hyperandrogenism and insulin resistance promote chronic inflammation and increased Reactive Oxygen Species (ROS), leading to oxidative stress, gut microbiome alterations, and metabolic dysfunction. PCOS is a multifactorial disorder influenced by hormonal imbalance, chronic inflammation, and oxidative stress. Lifestyle modifications, particularly tailored exercise regimens and nutritional strategies, play a critical role in mitigating these factors.